Eros : god of love - Temple, Teri.; Squier, Robert (Mankato, MN : Child's World, 2013)
An introduction to Greek mythology that shares the stories and myths about the Greek god Eros, god of love.
Includes bibliographical references (p. 32) and index.
Library Media Connection
Library Media Connection, May 2013
6.1
3-6.
3-6
Keywords: Eros (Greek deity) -- Juvenile literature; Mythology, Greek -- Juvenile literature; Eros (Greek deity); Mythology, Greek; Eros (Greek deity); Greek mythology